PENGARUH KONSUMSI BUAH PEPAYA (CARICA PAPAYA) TERHADAP KEJADIAN KONSTIPASI PADA LANSIA - Dewi Anggraini; Maya Susiana Candrawati (Jurnal Kesehatan STIKes IMC Bintaro, 2022)
With increasing age in the elderly there are various physical and psychosocial changes, many older people whose daily needs are not met such as eating only modestly and rarely doing activities because of the condition that many elderly experience digestive disorders resulting in constipation. If constipation is not immediately treated, colon cancer will occur by consuming fiber to reduce the incidence of constipation, papaya fruit in addition to the fiber content there are also enzymes of papain and chymopapain function to soften the stool so that feces are not hard and easy to remove. The purpose of this study was to determine the effect of papaya fruit consumption on the incidence of constipation in the elderly in the RT.002 RW.006 Parigi Lama area - South Tangerang. The research methodology in this study uses a quantitative approach to the type of research Quasy Experiment Design, One Group Pretest Posttes Design. Quota Sampling technique with a sample of 32 elderly. Statistical tests using the Paired Samples T-test. The results of the study before papaya fruit consumption were moderate constipation (56.3%), mild (28.1%) and severe (15.6%). After consumption of papaya fruit is mild constipation (62.5%), moderate (15.6%) and normal (21.9%). Data analysis using Paired Samples T-test showed p value 0,000 or p <0.05. The conclusion is that there is a significant influence between before and after the effect of papaya fruit consumption on the incidence of constipation in the elderly in the RT. 002 RW. 006 Parigi Lama Pondok Aren - South Tangerang area.